Military Conflict and Neo-Liberalization in Israel (2001–2006): A Neo-Gramscian Approach. (May 2018) - Avigur-Eshel, Amit; Filc, Dani
Existing analytical frameworks for the study of Israel's political sociology and political economy tend to view the Israeli society as polarized into a neo-liberal secular and peace-seeking elite and religious ethno-republican social groups. The turn to ethno-republicanism following the outbreak of the Second Intifada in 2000, and two neo-liberal economic programs in 2002 and 2003, exposed the limitations of those approaches. We suggest that a Neo-Gramscian approach provides a better theoretical framework for the analysis of the early years of the twenty-first century. We argue that during the years 2001–2006 a hegemonic project was constituted which succeeded in combining neo-liberal and ethno-republican elements. This project was based on a relatively stable socio-political alignment of social groups, primarily drawn from the Jewish middle class. In order to establish our argument, we characterize the project and analyze the position of the main social groups in Israeli society relative to it.